PEMIKIRAN BAKR BIN ABDULLAH DAN ABDUL QADIR BIN ABDUL AZIZ TENTANG ADAB DAN AKHLAK PENUNTUT ILMU - Anshori, Ari; Fanany, Abdullah Ali (Profetika Jurnal Studi Islam, 2017)
The background of this study is that the study is closely related to morals and manners, the companions of Allah's Apostle Shallallahu alaihi wasallam began studying to learn manners and morals. Having manners and morals will make easy science to be learned from a teacher, so blessing and will be absorbed into the benefits of life. Knowing the purpose of this study is the concept of the sheikh Bakr bin Abdullah and Shaykh Abdul Qadir bin Abdul Aziz on manners and morals prosecution of science. Tracing paper is Ḥilyah Ṭālib al-‘Ilm sheikh Bakr and works sheikh Abdul Qadir Al Jāmi` fī Ṭolabil `Ilmisy Syarīf. As well as knowing the differences and similarities view of Sheikh Bakr bin Abdullah and Sheikh Abdul Qadir Abdul Aziz on manners and morals prosecution of science. Difficulties encountered in this study is a book by Shaykh Abdul Qadir bin Abdul Aziz Al Jāmi` fī Ṭolabil `Ilmisy Syarīf unsold `free. He was a prisoner and was sentenced to life imprisonment by the Egyptian government because its association with global jihad. The method used is the literature using this type of comparative research, the approach used in this study is a philosophical approach, which is to examine the figures and reveal the thinking behind the visible nature of things. Methods of data collection in this study using the method of document review. The results showed that the First: Comparison of manners and morals prosecution of science in the eyes of the sheikh Bakr and Sheikhs Abdul Qadir refer book Ḥilyah Ṭālib al-‘Ilm and book Al Jāmi` fī Ṭolabil `Ilmisy Syarīf does not have much difference. Both are consistent with the Qur'an and Sunnah, as well as determine the good and bad morals through the Qur'an and the Sunnah and not others. Second: Second: the conclusion of the book Al Jāmi` fī Ṭolabil `Ilmisy Syarīf by Sheikh Abdul Qadir morals relating to `Alim and Muta'alim is sincere in the intention, really use the time, occupy yourself with your most important science, right in choosing the source (reference) book, beginning with science, patience to study and teach it. Third: The conclusion of book Ḥilyah Ṭālib al-‘Ilm is a self-contained in the claimant of science such as Science is worship, follow the path of the salafus ṣolih, always fear Allah Subhānahu wa ta'ālā. Manners in the scientific life of the spirit in science, passionate in studying, traveling far in their studies, keep the knowledge in writing. Invalidate-canceling this provision include resentment, envy, prejudice, sit together heretical, stepped to the forbidden. Latar belakang penelitian ini adalah bahwa menuntut ilmu berkaitan erat dengan akhlak dan adab, para sahabat Rasulallah Shallallahu alaihi wasallam mulai menimba ilmu dengan belajar adab dan akhlak. Memiliki adab dan akhlak akan menjadikan mudahnya ilmu yang akan dipelajari dari seorang guru, sehingga berbarokah dan akan terserap menjadi manfaat dalam hidup. Tujuan penelitian ini adalah Mengetahui konsep syeikh Bakr bin Abdullah dan syeikh Abdul Qadir bin Abdul Aziz tentang adab dan akhlak penuntut ilmu. Menelusuri karya syeikh Bakr yaitu Ḥilyah Ṭālib al-‘Ilm dan karya syeikh Abdul Qadir Al Jāmi` fī Ṭolabil `Ilmisy Syarīf. Serta mengetahui perbedaan dan persamaan pandangan Syeikh Bakr bin Abdullah dan Syeikh Abdul Qadir Abdul Aziz tentang adab dan akhlak penuntut ilmu. Kesulitan yang dihadapai dalam penelitian ini yaitu buku karya syeikh Abdul Qadir bin Abdul Aziz Al Jāmi` fī Ṭolabil `Ilmisy Syarīf tidak terjual bebas. Beliau menjadi tahanan dan divonis penjara seumur hidup oleh pemerintah Mesir sebab keterkaitannya dengan jihad global. Metode penelitian yang digunakan adalah kepustakaan (library research) menggunakan jenis penelitian perbandingan atau komparatif, pendekatan yang digunakan dalam penelitian ini adalah pendekatan filosofis, yaitu untuk meneliti pemikiran tokoh dan mengungkapkan dibalik hakikat segala sesuatu yang nampak. Metode pengumpulan data dalam kajian ini menggunakan metode telaah dokumen. Hasil penelitian menunjukkan bahwa Pertama: Perbandingan adab dan akhlak penuntut ilmu menurut pandangan syeikh Bakr dan syeikh Abdul Qadir merujuk pada buku Ḥilyah Ṭālib al-‘Ilm dan buku Al Jāmi` fī Ṭolabil `Ilmisy Syarīf tidak memiliki perbedaan yang jauh. Keduanya bersesuaian dengan al Qur’an dan as Sunnah, serta menentukan baik dan buruk akhlak melalui al-Qur’an dan Sunnah, bukan yang lain-lainnya. Kedua: kesimpulan buku Al Jāmi` fī Ṭolabil `Ilmisy Syarīf karya syeikh Abdul Qadir adab-adab yang berkaitan dengan Alim dan Muta’aalim ialah ikhlas dalam niat, betul-betul memanfaatkan waktu, menyibukkan diri dengan ilmu-ilmu yang paling penting, tepat dalam memilih sumber (referensi) buku, berawal dengan ilmu, sabar untuk menuntut ilmu dan mengajarakannya. Ketiga: Kesimpulan buku Ḥilyah Ṭālib al-‘Ilm karya syeikh Bakr ialah: Adab-adab diri penuntut ilmu diantaranya Ilmu adalah ibadah, ikutilah jalan para salafus ṣolih, selalu takut kepada Allah Subhānahu wa ta’ālā. Adab dalam kehidupan ilmiah diantaranya semangat tinggi dalam ilmu, bergairah dalam menuntut ilmu, melakukan pekerjaan jauh dalam menuntut ilmu, menjaga ilmu secara tertulis. Pembatal-pembatal bekal ini diantaranya dendam, dengki, buruk sangka, duduk bersama ahli bid'ah, melangkahkan kaki kepada yang diharamkan.